Uji Potensi Eco-Enzyme Terhadap Pertumbuhan Tanaman Sawi Hijau (Brassica chinensis var. Parachinensis) Dengan Menggunakan Teknik Hidroponik - Yunanda, Novia; Furqan, Muhammad; E, Erlita (Madani: Jurnal Ilmiah Multidisiplin, 2024)
Agricultural sector production requires large areas of land, while farmers who have limited land find it difficult to produce vegetable crops. The use of non-soil media that is suitable for use is hydroponics. Cultivating vegetable plants that are currently needed by the community using a hydroponic system is one of the green mustard plants (Brassica chinensis var. Parachinensis). To produce maximum growth, additional organic liquid fertilizer is needed, one of which is Eco-Enzyme. Eco-enzyme is a solution of complex organic substances produced from the fermentation process of organic waste, sugar and water which has benefits, one of which is as plant fertilizer. This research aims to determine the differences produced by Eco-Enzyme on the growth of green mustard plants (Brassica chinensis var. Parachinensis) using hydroponic techniques. The research method used a Randomized Block Design (RAK) with one factor, namely ecoenzyme concentration with 5 treatments and 5 repetitions, including E0 (0 ml/L water); E1 (2.5 ml/L water); E2 (5 ml/L water); E3 (7.5 ml/L water); and E4 (10 ml/L water). The parameters observed were plant height, number of leaves, root length, and wet biomass of mustard greens. Nutrient content data was analyzed descriptively, while plant growth data was analyzed using one-way ANOVA, followed by the Duncan Test at the 5% level. The research results show that the nutrient content of ecoenzymes is included in the very low criteria, namely N=0.07%; P=0.04%; and K=0.004%. Providing ecoenzymes as liquid organic fertilizer of various concentrations has a significant effect on plant growth, namely plant height, number of leaves, root length and wet biomass of mustard plants. The optimal concentration that influences the growth of mustard greens is 10 ml/L from the E4 treatment